The Impact of Accounting Information System on Organizational Performance: Evidence from Bangladeshi Small & Medium Enterprises - Hosain, Md Sajjad (Journal of Asian Business Strategy, 2019)
The study has performed an investigation to identify the impact of accounting information system (AIS) on organizational performance (profitability) for Bangladeshi small & medium enterprises (SMEs). For due purpose, three components of AIS has been selected with help of literature: accounting knowledge (AK), management support (MS) and record keeping performance (RKP). The dependent variable was measured based on the profitability reported by the owners. A structured questionnaire has been utilized to collect data from 803 respondents working as mid and top level managers at 341 Bangladeshi SMEs who were previously selected through convenience sampling method. In order to reveal the relationships, multiple correlation and regression analysis have been conducted. The findings revealed that AK and RKP have strong positive correlations with organizational performance while MS has a positive but moderate relationship with the reported profitability of those SMEs. The results are expected to be beneficial for further research in wider scope in future.